Going Online: Decision Processes of Community College Students Enrolling in Online Degree Programs - Hill, Michael; Hart, Cassandra (Online Learning, 2026)
This paper examines the decision-making process of students who enroll online at two California community colleges to learn how fully-online students gather information about potential institutions and programs, which alternatives were considered, and which sources were most useful to them in choosing programs. We draw on interviews with 25 students intending to attend fully online; interviews were conducted prior to the COVID-19 pandemic. These findings suggest that students are aware of the availability of online classes and make the choice to attend at a given institution based on convenience, finances, and familiarity with the college. The students that we interviewed almost all enrolled in programs that were proximate to their homes, despite their intent to complete their academic programs online. Colleges should think carefully about how information and support are provided to those students wishing to complete classes and find creative ways to engage students and provide campus resources virtually.